2011
DOI: 10.1016/j.bbr.2011.01.048
|View full text |Cite
|
Sign up to set email alerts
|

Resting frontal gamma power at 16, 24 and 36 months predicts individual differences in language and cognition at 4 and 5 years

Abstract: Gamma activity has been linked to a variety of different cognitive processes and exists in both transient and persistent forms. Across studies, different brain regions have been suggested to contribute to gamma activity. Multiple studies have shown that the function of gamma oscillations may be related to temporal binding of early sensory information to relevant top-down processes. Given this hypothesis, we expected gamma oscillations to subserve general brain mechanisms that contribute to the development of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
102
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(114 citation statements)
references
References 76 publications
10
102
2
Order By: Relevance
“…Age-related changes in resting state neural synchronization have been observed (Boersma et al, 2011(Boersma et al, , 2013, and developmental changes in task-dependent modulation of local oscillations have been previously described (Clarke et al, 2001). Maturational changes in spontaneous local EEG gamma oscillations during infancy and early childhood are associated with the development of language abilities (Benasich et al, 2008;Gou et al, 2011). The present study builds on such work by establishing, for the first time, age-related changes in neuronal network synchronization in language processing.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Age-related changes in resting state neural synchronization have been observed (Boersma et al, 2011(Boersma et al, , 2013, and developmental changes in task-dependent modulation of local oscillations have been previously described (Clarke et al, 2001). Maturational changes in spontaneous local EEG gamma oscillations during infancy and early childhood are associated with the development of language abilities (Benasich et al, 2008;Gou et al, 2011). The present study builds on such work by establishing, for the first time, age-related changes in neuronal network synchronization in language processing.…”
Section: Discussionsupporting
confidence: 55%
“…Modulation of neural oscillations, and their coordination across brain areas, have been linked to expressive language, receptive language, and the interactions between language networks and brain regions mediating other cognitive and perceptual abilities (i.e. Bastiaansen et al, 2005;Bedo et al, 2014;Bögels et al, 2014;Doesburg et al, 2008Doesburg et al, , 2012Ewald et al, 2012;Hermes et al, 2014;Mellem et al, 2013;Piai et al, 2013;Weiss & Mueller 2012), and local neural oscillations have been related to the encoding of speech sounds as well as the development of language abilities during infancy and early childhood (Benasich et al, 2008;Gou et al, 2011). Whether inter-regional coherence changes throughout childhood and adolescence, as well as if such changes are related to the development of language abilities, remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Maturation of neural synchrony in each stage is compatible with changes in the myelination of cortico-cortical connections and with development of GABAergic neurotransmission (Uhlhaas, Roux, Rodriguez, Rotarska-Jagiela, & Singer, 2010; Singer, 1995). In babies 16 to 36 months of age, gamma oscillation power is associated with language, cognitive and attention measures in children and can predict cognitive and linguistic outcomes through five years of age (Gou, Choudhury, & Benasich, 2011; Benasich, Gou, Choudhury, & Harris, 2008). In addition, induced gamma band activity becomes prominent around 4.5 years of age in children who have had 1 year of music training, but not in children of this age who have not been trained (Trainor, Shahin, & Roberts, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Gómez et al (2013) also reported an increase in power at gamma frequencies of resting-state MEG recordings. Importantly, maturation of such power spectra has been linked to development of abilities such as language with such associations being observed as early as infancy (Benasich et al 2008;Gou et al 2011). …”
Section: Spectral Power and Developmentmentioning
confidence: 99%